Fair Play—A Necessity in Higher Education Exit Exams: A Systematic Review - Samson Worku Teshome (ANWARUL, 2025)
This systematic literature review critically examines the equity and inclusivity implications of exit exams in higher education, synthesizing evidence from 33 studies published between 1994 and 2024. While exit exams aim to standardize academic accountability and ensure graduate competency, their implementation often exacerbates disparities among marginalized student populations, including racial and ethnic minorities, low-income students, and individuals with disabilities. The review employs the PRISMA framework to analyze qualitative, quantitative, and mixed-method studies, revealing that high-stakes exit exams frequently induce stress, narrow curricular focus, and disproportionately hinder underrepresented groups. Key findings highlight systemic inequities in exam design, accessibility, and washback effects on pedagogy, with marginalized students facing heightened barriers to success. The study identifies divergent outcomes across demographic groups, underscoring the tension between academic rigor and equitable assessment practices. Thematic analysis emphasizes the need for policy reforms, such as culturally responsive exam design, alternative assessment models, and institutional support mechanisms to mitigate adverse impacts. Recommendations include integrating formative assessments, adaptive testing, and holistic evaluation frameworks to balance accountability with inclusivity. This review contributes to the discourse on educational equity by advocating for systemic changes in exit exam policies and urging stakeholders to prioritize accessibility and fairness. By addressing these challenges, higher education institutions can foster inclusive environments that align assessment practices with the diverse needs of all students, ultimately promoting equitable academic and professional outcomes.